DEVELOPMENT OF ECOLOGICAL CULTURE ON THE BASIS OF MODERN PEDAGOGICAL TECHNOLOGIES - Ismoilova Gulbaxor Azamovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article talks about the formation of ecological culture in students, a reflection on issues of Ecology and nature protection, its historical development processes, and future prospects.